Educação e lutas sociais na colonização dirigida: o Alto Turi maranhense: 1962-1984 - Manhães, Luiz Carlos Siqueira (1987)
The understanding of relationship between education and social fights on historical context of directed colonization is proposed. The field work took place at Alto Turi, in the Pre Amazonia region of Maranhão, where the Alto Turi colonization Project (PCAT) is undertaken by Companhia de Colonização do Nordeste (COLONE), a mixed enterprize subsidiary to Superintendencia do Desenvolvimento do Nordeste (SUDENE). The fundamental question here is concerned to changes the settlers attain through education, from passive producers and dependent on paternalistic and assistencial relationships, to active individuals ready to discuss and propose changes to the PCAT. Their education process, reflexion and actions analysis pervades the understanding of historical process of Maranhão Alto Turi, i. e.: North-eastern migration movement begun in the fifties; SUDENE's answer to this movement, in 1962, when regional colonization project was created; the undergoing migration process which introduced new performers (farmes and traders); the creation of COLONE in 1972 to replace SUDENE in the development of PCAT communities organizing work analysis, education, rural extension and co-operativism offercd formerIy by SUDENE and afterwards by COLONE to the nucleated populations. This way of working implies yet in the analysis of the regional classes structure, verifying the political role and the social power of the settlers' group, as well as understanding the contradictions that dynamize the classes fight in the region and noting this movernent inside a broader social process, regional and national.